Normative properties of stock market equilibrium with moral hazard - Martine Quinzii; Michael Magill (University of California, Department of Economics, 2006)
This paper presents a model of stock market equilibrium with a finite number of corporations and studies its normative properties. Each firm is run by a manager whose effort is unobservable and influences the probabilities of the firm's outcomes. The Board of Directors of each firm chooses an incentive contract for the manager which maximizes the firm's market value. With a finite number of firms, the equilibrium is constrained Pareto optimal only when investors are risk neutral and firms' outcomes are independent. The inefficiencies which arise when investors are risk averse, or when firms are influenced by a common shock, are studied and it is shown that under reasonable assumptions there is under investment in effort in equilibrium. The inefficiencies exist when the firms are not completely negligible, as is typical of the large corporations with dispersed ownership traded on public exchanges in the US. In the idealized case where firms of each type are replicated and replaced by a continuum of firms of each type with independent outcomes, the inefficiencies disappear.
Keywords: 330